Procurement-Cum-Maintenance of Locomotives Model Agreement - Planning Commission (Planning Commission, 2009)
During the past five years, the Indian Railways have significantly improved their commercial outlook and increased the profitability of their operations. Following this turn-around, the Railways have initiated an ambitious plan for augmentation of capacity and modernisation of its rolling stock, especially the locomotives and passenger coaches. It has also initiated the construction of a Dedicated Freight Corridor on the Delhi-Mumbai and Ludhiana-Howrah route. For improving and expanding container operations, the Railways have already allowed fourteen competing companies to operate container trains which were earlier operated by the Railway-owned Container Corporation that functioned as a monopoly. Yet, much remains to be done in terms of modernisation of technology, rolling stock and railway tracks. Creation of additional capacity at economical costs and within a given time-frame remain critical issues in the implementation of Railway projects.
Planning Commission Government of India
Planning Commission Government of India